2020
DOI: 10.1099/ijsem.0.004075
|View full text |Cite|
|
Sign up to set email alerts
|

Wickerhamiella osmotolerans sp. nov. and Wickerhamiella tropicalis sp. nov., novel ascomycetous yeast in the family Wickerhamiellaceae

Abstract: The GenBank/EMBL/DDBJ accession numbers for the D1/D2 domain of the LSU rRNA gene and ITS region determined in this study are MH141490 and MN194615 for DMKU VGT1-14 T and MH142264 and MN218416 for DMKU VGT1-19 T. The MycoBank number of Wickerhamiella osmotolerans sp. nov. is MB 833394 and that of Wickerhamiella tropicalis sp. nov. is MB 833393. Supplementary figure is available with the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…W. australiensis, W. cactophila, W. jalapaonensis, W. kiyanii, W. kurtzmanii, W. occidentalis and W. pagnoccae) [21][22][23]; nectar (W. natalensis and W. nectarea) [6]; fruit (W. fructicola) [22]; plant leaves (e.g. W. goesii, W. slavikovae and W. siamensis) [8,24]; insects (W. allomyrinae, W. dianesei, W. queroliae, W. natalensis and W. nectarea) [6,10,21]; wineries and distilleries (W. cachassae, W. dulcicola and W. shivajii) [11,25]; grease traps (W. osmotolerans and W. tropicalis) [13]; and seawater (W. osmotolerans) [13]. Some species have been recovered from human sources (e.g.…”
Section: Novel Species Identification and Delineationmentioning
confidence: 99%
See 2 more Smart Citations
“…W. australiensis, W. cactophila, W. jalapaonensis, W. kiyanii, W. kurtzmanii, W. occidentalis and W. pagnoccae) [21][22][23]; nectar (W. natalensis and W. nectarea) [6]; fruit (W. fructicola) [22]; plant leaves (e.g. W. goesii, W. slavikovae and W. siamensis) [8,24]; insects (W. allomyrinae, W. dianesei, W. queroliae, W. natalensis and W. nectarea) [6,10,21]; wineries and distilleries (W. cachassae, W. dulcicola and W. shivajii) [11,25]; grease traps (W. osmotolerans and W. tropicalis) [13]; and seawater (W. osmotolerans) [13]. Some species have been recovered from human sources (e.g.…”
Section: Novel Species Identification and Delineationmentioning
confidence: 99%
“…W. verensis) [12]. Of these, most species appear to be endemic to tropical regions (W. cacticola, W. dianesei, W. dulcicola, W. fructicola, W. goesii, W. kiyanii, W. occidentalis, W. osmotolerans, W. pagnoccae, W. queroliae, W. shivajii, W. siamensis and W. slavikovae), while other species have a cosmopolitan distribution [7,10,11,13,[22][23][24]26]. In the current study, the novel Wickerhamiella species was isolated from different habitats viz.…”
Section: Novel Species Identification and Delineationmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Wickerhamiella consists of species that exhibit nutritional specialization are mostly associated with flowers, fruits, leaves and insects. Forty-three Wickerhamiella species are known, with some exhibiting a cosmopolitan distribution, and others living in specialized habitats in ecosystems of the Neotropics and Asia [1][2][3][4][5]. Most species do not ferment glucose or produce filamentous growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that yeast can be found in diverse habitats such as soil [1], sea [2], parts of plants [3], insects [4] and waste [5][6][7][8][9][10]. The waste habitat offers a variety of environments and nutrient content and therefore it has become an interesting resource due to the many novel yeasts that have been discovered there.…”
mentioning
confidence: 99%